Efficacy and Safety of Bepirovirsen in Chronic Hepatitis B Infection - Yuen, Man-Fung; Lim, Seng-Gee; Plesniak, Robert; Tsuji, Keiji; Janssen, Harry L.A.; Pojoga, Cristina; Gadano, Adrian; Popescu, Corneliu P.; Stepanova, Tatyana; Asselah, Tarik; Diaconescu, Gheorghe; Yim, Hyung Joon; et al. (The New England journal of medicine, 2022)
In a phase 2 trial, bepirovirsen, an antisense oligonucleotide that targets all hepatitis B virus mRNAs, resulted in sustained loss of hepatitis B surface antigen and HBV DNA in 9 to 10% of participants with chronic HBV infection.